Tissue culture and cellular behaviour studies of rice (Oryza sativa L. CV. MRQ 74) / Azani Saleh - Azani, Saleh (2017)
Tissue culture or in vitro studies of rice (Oryza sativa L. cv. MRQ 74) locally known as “padi Mas Wangi” has been successfully investigated in this project. Callus induction was obtained on MS media supplemented with various concentrations of 2,4-D, applied singly and in combinations with BAP. Stem was identified as the most responsive explant, followed by root, while leaf explants failed to produce any callus. The highest means of callus dry weight of stem (71.60 ± 6.40 mg) and root (66.70 ± 10.90 mg) explants were recorded on MS media supplemented with 0.5 mg/L 2,4-D and 0.5 mg/L 2,4-D in combination with 0.5 mg/L BAP, respectively. Stem explants produced either creamy white, globular and compact or creamy white, globular and friable callus. On the other hand, creamy white, globular and sticky or mucilageneous callus was observed from root explants. Somatic embryos were induced by transferring the obtained callus from MS media supplemented with 2.0 mg/L BAP in combination with 1.0 mg/L 2,4-D onto MS media containing various concentrations of ABA, kinetin and L-Proline. MS media supplemented with 1.0 mg/L ABA in combination with 1.0 mg/L kinetin showed the highest mean number of somatic embryos (14.33 ± 0.27). The addition of 400 mg/L L-Proline had significantly (P<0.05) increased the mean number of somatic embryos (17.37 ± 0.66). Stem was found to be the only responsive explant for in vitro regeneration of this species. The best hormone for shoot induction was BAP at the concentration of 1.5 mg/L with mean number of shoots per explant of 4.03 ± 0.31. The highest mean number of roots produced (25.33 ± 1.89) was achieved when stem explants were cultured on MS media supplemented with 0.1 mg/L BAP in combination with 0.1 mg/L NAA. The addition of TDZ at the concentration of 0.1 mg/L had significantly increased the mean number of shoots per explant (8.23 ± 1.09). Synthetic seeds were created from microshoots of stem explants that were cultured on MS media containing 1.5 mg/L BAP. The best encapsulation matrix was Ca-free MS supplemented with 30 g/L sucrose with survival rate of 100 %, after 30 days of culture. The survival rate of plantlets (100 %) were best achieved on MS basal and MS media supplemented with 0.1 mg/L BAP. It was found that the viability of seeds decreased from 93.33 % to 3.33 % after one month of storage at 4 oC. Regenerated plantlets from stem explants cultured on MS media containing 0.5 mg/L 2,4-D were successfully acclimatized on all types of growing substrates with different survival rates of plantlets. A combination of black soil and red soil at a ratio of 1:1, showed the highest survival rate after 4 and 8 weeks of acclimatization, 90.00 ± 1.53 % and 83.33 ± 1.20 %, respectively. Cytological studies revealed that Mitotic Index (MI) values of root tip meristem cells was significantly lower in MS media supplemented with NAA, kinetin and 2,4-D as compared with hormone-free MS. The obvious effect of 2,4-D was observed on nuclear DNA content, mean cell and nuclear areas.